Reimagining Delilah's Afterlives As Femme Fatale: The Lost Seduction - Blyth, Caroline (Library of Hebrew bible/Old Testament studies, 2017)
Cover -- Half Title -- Series -- Title -- Copyright -- Dedication -- Contents -- Figures -- Acknowledgements -- Abbreviations -- Introduction -- Chapter 1 The Femme Fatale: Cultural Icon -- The Dusk Hours of the Nineteenth Century: Femmes Fatales in the Fin de Siècle -- The (Sexualized) Female of the Species Is More Deadly than the Male -- Gender bending Femmes -- The Earthly Chimera -- Erotic Exotics -- Origins of the Fin de Siècle Femme Fatale -- Reflecting Back and Looking Ahead -- A Dame to Die for: The Femme Fatale in Hard-boiled Fiction and Film Noir -- Exquisite Violence -- Queer Noir Femmes -- A Hard-boiled Otherness -- Damsels in Disguise and Duplicitous Dames -- The Dame's Demise -- Sites of Contention: The Origins of Hard-boiled and Noir Femmes Fatales -- Saying Au Revoir - But Not for Too Long -- Sexed Up and Gender Fluid: The Fatal Woman in the Twentieth Century Fin de Siècle and Beyond -- 'Flesh Seduces. Passion Kills' -- Lost in the Post-feminist: Gender Subversion and the Neo-noir Femmes Fatales -- Getting Away with Murder -- Fin de Siècle Anxieties Redux: Origins of the Neo-noir Femme Fatale -- Summing Up the Femme Fatale -- Chapter 2 Mind The Gap Part 1: Delilah's Interpretive Afterlives -- Introduction -- What's in a Name? -- Gendering Sex -- Did They or Didn't They? -- Gender Trouble? -- Whoring Around -- 'I Am Philistine, and Beautiful': Race, Hybridity and Otherness -- Show Me the Money: Unravelling Delilah's Motivations -- (Un)happy Endings: Delilah's Fate -- Lingering Impressions -- Chapter 3 Mind The Gap Part 2: Delilah's Cultural Afterlives -- Fatal Words: Delilah as Femme Fatale in Literature -- Captured on Canvas: Delilah in Art -- Peter Paul Rubens, Samson and Delilah (c. 1609-10) -- A Coterie of Delilahs from Gustave Moreau -- Alexandre Cabanel, Samson and Delilah (1878).